Gestão da água como bem comum: uma revisão de estudos Nacionais e Internacionais - Silva, Camila de Assis (2025)
The general objective of this thesis is to understand how the theory of the commons is perceived in studies on water management. The study is justified by the importance of the common good, which refers to the sovereign good of communities and guides individuals social actions so that this good is established as an idealizer of just norms. The study was conducted through bibliographic and documentary research. In this way, Part I presented the contextualization of the proposed theme, as well as the theoretical framework and methodological procedures. Part II is organized into four articles, consisting of three integrative literature reviews and one bibliometric study. In Part III, a synthesis was developed based on the categories discussed from the perspective of the common good, which emerged from the reading and analysis of the four studies presented. Part IV addressed the final considerations and a proposed future research agenda. From this perspective, Article 1 aimed to conduct an integrative literature review on the common good using the Web of Science database. The results indicated that the categories of analysis contributed to understanding the common good and revealed divergent perspectives on the term, highlighting its interdisciplinarity and heterogeneity. Article 2 aimed to analyze the understanding of water as a common good in international studies through an integrative review. The results revealed various interpretations and disputes over water in different countries, as well as diverse perspectives on the common good. Article 3 sought to understand the scientific field of water as a common-use resource, identifying the intellectual and conceptual structures developed on the subject in the international context. The results showed that the categories of analysis are interconnected due to their relationships with mercantilist perspectives and principles of collectivity, whether through “struggles” triggered by private interests or the recognition of the human right to water. Article 4 aimed to analyze the understanding of water management in Brazil based on national studies, through an integrative review conducted using the SciELO database. The analyzed studies addressed the complex process of water management in the country, highlighting institutional and structural obstacles that directly impact deficiencies related to basic sanitation and water supply. In general, the main theoretical contribution relates to the synthesis of categories, which revealed that the management of common goods, based on the principles of collectivity and democracy, can foster a participatory commitment among individuals in monitoring these resources. In practice, the aim was to contribute to raising individuals awareness regarding water consumption and to draw the government’s attention to the strengthening of public policies focused on this issue, suggesting themes for future research.